EXTERNAL MOTIVATION COMPETENCES OF MANAGERS IN IMPROVING PERFORMANCE ACCORDING TO PERCEPTIONS OF SPORTS EMPLOYEES - Karakaya, Yunus Emre; Karademir, Tamer; Yavuz, Cumaali (My University, 2019)
Just as in many institutions, motivation is of utmost importancein sports institutions as well. The sports managers’ abilities to motivatetheir employees in these institutions play a major role in achieving theexpected aims in sports. Sports managers, who can establish aneffective communication with their employees, can empathize with themand motive them, are more successful in their duties. Sports managers,who can motivate their employees, also contribute to in improving theperformance expected from sports. The aim of the study conductedwithin this framework is to determine the external motivationcompetencies of managers in improving their employees’ performancesaccording to the perceptions of sports employees, who work in theDirectorate of Youth Services and Provincial Directorate of Youth andSports in Turkey. The study group consists of 65 individuals working inthe Directorate of Youth Services and Provincial Directorate of Youthand Sports, who were chosen by the cluster sampling method andparticipated in the study voluntarily. The survey form developed by theresearchers was used as the data collection tool in the study. TheCronbach-Alpha internal consistency coefficient of the survey form wasdetermined to be 0.941. The data collected from the study group wasinvestigated for its normality distribution before it was subjected toanalyses. Because the data did not provide parametric tests assumptions, non-parametric tests, Mann Whitney U test for twosample comparisons and Kruskal Wallis test for multiple samplecomparisons, were used. The statistical significance level wasdetermined to be p<0.05. In conclusion, significant differences weredetermined in the survey matters for the variables of gender, age,education level and professional seniority. As a result of the datacollected within the scope of the study, it was determined that theemployees’ external motivation levels were at a moderate level.
Keywords: Eğitim; Eğitim Araştırmaları; Sosyoloji; Spor Bilimleri; Psikoloji